The Role of Medical Culture in the Development of Society (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article analyzes modern sociocultural processes. The role of medical culture in the development of society is revealed. Particular attention is paid to the development of bioethics, its sections, as well as the praxeological aspect of medical culture.